Analysis of water quality for seaweed cultivation in the southern and northern coastal waters of Sikka Regency - Maria Theresia Dua Tei; Barnabas P.P. Wini Bhokaleba; Neccia Yurike Patrisia (Fakultas Perikanan dan Ilmu Kelautan Universitas Borneo Tarakan, 2026)
Water quality is an important factor that determines the success of seaweed cultivation. Sikka Regency has significant aquatic potential for seaweed cultivation development, but the decline in production and ecological disturbances are issues that need to be examined through water quality evaluation. This study aims to analyze the water quality conditions and assess their suitability for seaweed cultivation sites in the waters of Sikka Regency, East Nusa Tenggara Province. The research was conducted from May to August 2025 at five locations, namely the waters of Reroroja Village, Kolidetung, Kojadoi, Nenbura, and Wailamung. The parameters measured include temperature, pH, dissolved oxygen, salinity, and water transparency. Data were analyzed descriptively and quantitatively and compared with water quality criteria suitable for seaweed cultivation. The research results show that the temperature ranges from 20–35°C, pH 6–7, DO 5,2–9,8 mg/L, salinity 22–40 ppt, and water transparency 2,1–5,5 m. The research results indicate that the water quality parameters at five locations during the observation period are not entirely within the range suitable for seaweed growth in Sikka Regency, East Nusa Tenggara Province.